Studi Penghematan Energi Pada Gedung Tiga Lantai Di Kabupaten Padang Pariaman - Hidayatul Catra Burhan; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Life in the modern era like today is a life that is very dependent on the availability of energy. With the availability of energy, humans can create technology that alleviates human work. Unfortunately human dependence on energy is increasing and if overexplored it will have an impact on the energy crisis. The rise of energy saving campaigns by the government requires all people to carry out energy saving activities from small, medium, or large scale. The Polytechnic of Shipping of West Sumatra is a campus under the Ministry of Transportation of the Republic of Indonesia, located in Padang Pariaman Regency, West Sumatra. In this study the authors conducted a study and observation of electrical energy savings in the main building on the campus of the Polytechnic of Shipping of West Sumatra, where the energy savings obtained from this study amounted to 2,393.1 kWh / month Key word: energy, energy savings, the lighting